ETIKA GURU DALAM PROSES BELAJAR MENGAJAR - Ruslan, Ruslan (Al-Riwayah: Jurnal Kependidikan, 2016)
The teacher is a figure of people who has a respectable and noble position. It is, as the phrase al-Ghazali, Ã¢Â€Âœthe most glorious creature in the kingdom of heaven is a man who knows, practice and teaching. Teachers like the sun that illuminates him and others Ã¢Â€Âœ. Thus, teachers are believed to occupy key positions in education. Teacher or educator is also ta figure which will give effect to the pupils or students. Therefore, a teacher must be someone who can guide and emulated as a role model in terms of both personal knowledge and behavior. The ideal teacher should have a certain number of qualifications related to the physical, ethical or moral or scientific. Ethical terms are also often used in three inter-related differences. The first is a general pattern or way of life. The second is set of rules or Ã¢Â€Âœmoral codeÃ¢Â€Â, and the third is investigation about the way of life and rules of behavior.